2018
DOI: 10.1002/cctc.201800326
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Importance of Hydrochloric Acid as a Cocatalyst for Resorcinarene‐Capsule‐Catalyzed Reactions

Abstract: This survey of resorcinarene-capsule-catalyzed reactions demonstrates that HCl functions as ac rucial cocatalyst by increasing the capsule's inherentB rønsteda cidity to enableo raccelerate cationic reactions. The presence of HCla ppears to be withoutconsequences for other reactions.[a] J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…Synthesis of resorcinarene 1: Synthesis of resorcinarene 1 was carried out as previously described. 6 Synthesis of cyclization substrates 15 and 16: (−)-Caryophyllene oxide (6.00 g, 27.2 mmol) was dissolved in DCM (150 mL) in a two-neck flask. The solution was cooled to −78 °C and ozone was bubbled through until a blue color persisted; the mixture was then purged with oxygen until disappearance of the blue color.…”
Section: Synthesis Of Catalyst and Cyclization Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of resorcinarene 1: Synthesis of resorcinarene 1 was carried out as previously described. 6 Synthesis of cyclization substrates 15 and 16: (−)-Caryophyllene oxide (6.00 g, 27.2 mmol) was dissolved in DCM (150 mL) in a two-neck flask. The solution was cooled to −78 °C and ozone was bubbled through until a blue color persisted; the mixture was then purged with oxygen until disappearance of the blue color.…”
Section: Synthesis Of Catalyst and Cyclization Substratesmentioning
confidence: 99%
“…3(14) 21.3 3C4 -3895.1 9-4929(2) -2801.0(16) 23.8 4C6 -3494.5 10-5169(2) -3448. 1(16) 24.6 3C8 -4308.0(9) -5276(2) -1381.8 (15) 21.4 3C9 -3590.5 9-4810(2) 4.6(16) 24.1 4C12 -3280.9 9-7451(2) -1092.1 (15) 23.8 3C13 -4598.9 10-3457(2) -2064.6(17) 25.9 4C16 -4700.4 10-7645(2) -3113.8 1727.7 4C17 -3877.4 10-3187 3343.0(17) 31.1 4C19 -4195.3 10 72.2(6) 27.2 70.1 6N7 40.7 (8) 27.0(8) 37.4 91.3 (6) 30.6(8) 1.8 7C10 20.9 (7) 28.9 (8) 19.6(7) 0.5 711.1(6) 1.6(7) C1 21.8 (7) 23.0(8) 20.6(7) -0.2(6) 13.0(6) -0.6(6) C4 22.6(7) 27.2 (9) 22.7(8) 0.8 (6) 13.7(7) -1.3 (7) C6 27.4 (8) 26. 4(8) 25.0(8) 2.2 (7) 18.0(7) -0.7 7C8 18.7 725.5 (8) 22.4 70.1 713.2(6) -0.4 6C9 20.5 728.8 (9) 24.0(8) -6.0(6) 13.3 7-3.0(6) 3 was selected and mounted on a mylar loop in perfluoroether oil on an Bruker APEX-II CCD diffractometer.…”
Section: N7mentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, these results show that the reaction take places inside the cavity of CR 6 and in the presence of HCl as a cocatalyst. In fact, as shown in a recent report, the inherent acidity of CR 6 was not sufficient for the catalysis of the hydrolysis of acetals inside the capsule (Scheme ). No hydrolysis was observed, if the reaction in Scheme was performed in the absence of the HCl cocatalyst.…”
Section: Hexameric Resorcinarene Capsules As Catalystsmentioning
confidence: 83%
“…We found that an acid cocatalyst was required to activate the terpene substrate . In several other cases, the intrinsic acidity of the capsule was sufficient to initiate the reaction . In the initial report, a selective cyclization reaction was achieved using the monoterpene geranyl acetate as the substrate.…”
Section: Introductionmentioning
confidence: 99%